DICTADORES O DEMÓCRATAS CONSECUENCIAS DE LA DISTANCIA DE PODER PREVALENTE EN LA ORGANIZACIÓN LATINOAMERICANA - Montesino, Max U. (European Scientific Journal, ESJ, 2015)
Several impediments to democracy in groups, organizations, communities, and nations in Latin America are discussed in this article. These roadblocks can be traced to the mental models prevalent in the Latin American cultures. The main conclusion is that the Latino tends to be closer to the socio-cultural conditions that favor dictatorships and undermine democracy. More concretely, democratization in Latin America is limited by many variables. Chief among them are: Timidity toward organizational and social change, parochialism, orientation toward the past, preference for the status quo, hierarchy, power distance, classism, sectarianism, authoritarianism, vertical decision-making structures, organizational rigidity, and low social synergy. These features permeate the political cultures in Latin American countries, as well as their managerial cultures. These cultural peculiarities represent serious obstacles to the democratic transformation of organizations and societies in the region. Important changes in values, attitudes, and behaviors (among individuals, organizations, communities, and even nations) are necessary to overcome the impediments discussed here.